Liberals and conservatives: Non-convertible currencies. (8th September 2015) - Hibbing, John R.; Smith, Kevin B.; Alford, John R.
Abstract: Duarte et al. are correct that the social science enterprise would improve on several fronts if the number of politically conservative researchers were to increase; however, because they misunderstand the degree to which liberals and conservatives are dispositionally different, they fail to appreciate the full range of reasons that conservatives are reluctant to enter the modern social sciences.